Temporal dynamics of trematode intermediate snail host environmental DNA in small water body habitats. Issue 12 (30th October 2021) - Jones, Rhys Aled; Davis, Chelsea N.; Jones, Dewi Llyr; Tyson, Fiona; Davies, Emma; Cutress, David; Brophy, Peter M.; Rose, Michael T.; Williams, Manod; Williams, Hefin Wyn
Abstract: Abstract: Environmental DNA (eDNA) surveying has potential to become a powerful tool for sustainable parasite control. As trematode parasites require an intermediate snail host that is often aquatic or amphibious to fulfil their lifecycle, water-based eDNA analyses can be used to screen habitats for the presence of snail hosts and identify trematode infection risk areas. The aim of this study was to identify climatic and environmental factors associated with the detection of Galba truncatula eDNA. Fourteen potential G. truncatula habitats on two farms were surveyed over a 9-month period, with eDNA detected using a filter capture, extraction and PCR protocol with data analysed using a generalized estimation equation. The probability of detecting G. truncatula eDNA increased in habitats where snails were visually detected, as temperature increased, and as water pH decreased ( P < 0.05). Rainfall was positively associated with eDNA detection in watercourse habitats on farm A, but negatively associated with eDNA detection in watercourse habitats on farm B ( P < 0.001), which may be explained by differences in watercourse gradient. This study is the first to identify factors associated with trematode intermediate snail host eDNA detection. These factors should be considered in standardized protocols to evaluate the results of future eDNA surveys.